2020
DOI: 10.2463/mrms.mp.2019-0188
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Flow Dynamics Result in Low Wall Shear Stress and High Oscillatory Shear Index in Abdominal Aortic Dilatation: Initial <i>in vivo</i> Assessment with 4D-flow MRI

Abstract: Purpose: To characterize the non-laminar flow dynamics and resultant decreased wall shear stress (WSS) and high oscillatory shear index (OSI) of the infrarenal abdominal aortic dilatation, cardiac phase-resolved 3D phase-contrast MRI (4D-flow MRI) was performed. Methods: The prospective single-arm study was approved by the Institutional Review Board and included 18 subjects (median 67.5 years) with the dilated infrarenal aorta (median diameter 35 mm). 4D-flow MRI was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…Time-averaged WSS (TAWSS) and OSI patterns have been suggested as disease risk indicators, such as for atherosclerosis and aortic dilatation ( 1 , 5 , 37 ). Callaghan et al ( 1 ) presented a normal pattern and range of WSS from 4D Flow MRI across a large population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-averaged WSS (TAWSS) and OSI patterns have been suggested as disease risk indicators, such as for atherosclerosis and aortic dilatation ( 1 , 5 , 37 ). Callaghan et al ( 1 ) presented a normal pattern and range of WSS from 4D Flow MRI across a large population.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, recent studies have suggested that WSS is a potential biomarker for atherosclerosis, aortic dilatation, and aneurysm ( 1 , 5 , 37 ). WSS measurement also has improved risk stratification in patients with carotid and coronary artery disease ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that in areas where the aorta is dilated, the generation of laminar flow is disturbed and turbulent flow occurs, resulting in a reduction in WSS; [ 10 ] therefore, WSS is expected to decrease in areas where Vort and EL are high. In this study, the concordance rates between the intensity distribution of WSS and those of the other 2 parameters were low, indicating, albeit indirectly, that such relationships do exist.…”
Section: Discussionmentioning
confidence: 99%
“…A large OSI means that instantaneous WSS vectors fluctuate more compared with WSS in the mainstream direction at the calculated point during one cardiac cycle. 30 Flow studies using in vitro models and computational fluid dynamics (CFD) have shown promising results in calculating consistent WSS in true patient anatomic models. 31,32 Advances in postprocessing software have made WSS estimation using 4D flow MRI easier.…”
Section: Pathological Hemodynamics Related To Aneurysm Formationmentioning
confidence: 99%